Strategie interakcyjne lektorów, z którymi dorośli chcą pracować - Strzałka, Agnieszka (Neofilolog, 2019)
Knowing that there is a definite link between instructor – student interaction and students’ affect, as there is between affect and learning, the article pro-vides a look at the ways in which FL teachers address adult learners. Teaching adult learners in general constitutes a challenge since the group are especially sensitive to self image and easily get demotivated. Teacher’s behaviour, her attitude to the adult student and the atmosphere of learning are among the most important motivational factors for adults. The article is an attempt at presenting specific interactional strategies good teachers practice in order to motivate adults, offer them a sense of security and satisfy their face needs.